2009
DOI: 10.1558/cam.v6i1.73
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of the effects of patient information-elicitation style on clinician information-giving

Abstract: Although effective communication improves the quality of the relationships between patients and medical clinicians, resulting in better outcomes for patients, little is known about how patients influence that communication. Using a controlled, repeated measures design we investigated the role that patient question-asking plays in shaping the communication behaviors of health care providers. Medical students participated in simulated medical consultations with confederate patients adopting different information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several studies have shown that patients who ask more questions receive more information [5,17,24]. A metaanalysis of interventions designed to increase questionasking showed that patients who ask more questions report higher satisfaction with care [25].…”
Section: Multivariate Analysis Of Factors Influencing Effect Of Doctomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that patients who ask more questions receive more information [5,17,24]. A metaanalysis of interventions designed to increase questionasking showed that patients who ask more questions report higher satisfaction with care [25].…”
Section: Multivariate Analysis Of Factors Influencing Effect Of Doctomentioning
confidence: 99%
“…Patient questionasking has been highlighted as an important strategy for patients to obtain the information they need [1] and is an essential component of shared decision making [4]. Indeed, patient question-asking may enable patients to drive the agenda and thus focus the information exchange on their areas of priority and has been shown to be associated with greater information provision during medical consultations [1,5]. Physician endorsement of question-asking may enable or enhance patient question-asking during consultations.…”
Section: Introductionmentioning
confidence: 99%
“…6 Sandberg et al 7 illustrated that patient understanding and comprehension are key dimensions in the effectiveness of doctor-patient communication. The exchange of information that takes place between them is crucial both to the doctor understanding the patient and to the patient's comprehension of his or her health status, care and maintenance.…”
Section: Communicationmentioning
confidence: 99%
“…Patients have substantial influence on what is discussed. Those who ask more questions typically receive more answers from their physicians [5-7], and those who are more involved in their office visits adhere better to treatment recommendations [4]. Patients who actively seek information and participate more with their physicians report better health status at follow-up [8], have fewer functional limitations, and better health outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%